Rancangan Sumur Resapan Air Hujan sebagai Upaya Pengurangan Limpasan di Perumahan Samudera Afroza 3, Kota Jambi - Sindu Sanjaya; Lailal Gusri; Tri Syukria Putra (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
Land-use changes dominated by impervious surfaces in residential areas reduce the natural infiltration capacity of the soil and increase surface runoff, which may lead to flooding and waterlogging. This study aimed to design a rainwater infiltration well system as an effort to reduce surface runoff in Samudera Afroza 3 Housing Estate, Jambi City. A quantitative approach was employed through field surveys, hydrological analysis, soil permeability testing, GIS-based land-use analysis, and infiltration well design in accordance with SNI 8456:2017 and SNI 03-2453-2002 standards. Rainfall analysis was conducted using maximum daily rainfall data from 2014–2023, applying several probability distributions, with the Gumbel distribution identified as the most representative model. The results revealed that the residential area covers 8,104 m², with 91.84% of the land occupied by built-up surfaces, resulting in limited natural infiltration capacity. The average soil permeability value of 0.00024 m/s indicates favorable conditions for the implementation of infiltration wells. Based on the design calculations, 41 Type III infiltration wells are required, providing a total storage capacity of 289.665 m³ and an infiltration discharge of 0.0919 m³/s. The proposed infiltration well system is capable of reducing runoff volumes by 15.044%, 12.486%, and 11.223% for 2-year, 5-year, and 10-year return periods, respectively. Therefore, infiltration wells can be considered an effective alternative for water conservation and runoff management in residential areas.